TECHNOLOGY OF PROFESSIONAL-APPLIED PHYSICAL TRAINING STUDENTS TECHNICAL EDUCATIONAL INSTITUTIONS - Rymyk, R. V.; Malaniuk, L. B.; Leshchak, O. M.; Synytsia, A. V. (Rehabilitation and Recreation, 2021)
The article defines professional qualities, substantiates and formulates the content of professional-applied physical training of students of vocational and technical educational institutions, determines the means of professional-applied physical training of students and their effectiveness in the process of mastering the future profession. The purpose of the study is to determine the impact of professional and applied physical training on professionally important qualities and properties of students in technical schools. In order to accomplish the tasks, theoretical analysis and generalization of scientific and methodological literature, pedagogical observations, physiometric research, pedagogical testing, methods of mathematical statistics were used. The implemented experimental program included the means, forms and conditions for the implementation of this program. From the existing programs on physical education, it differed in specific means and methods of developing the professional qualities of specialists who carry a small amount of physical activity during their professional activity Effectiveness of our program of professional-applied physical training students of the VET, confirmed in the experiment, as evidenced by its results. Probably the indexes of testing of professional qualities of students of VET schools, such as coordination of movements according to the Kopylov test, have significantly increased (19,2%); jump in length from the front and back (15,8%); skill test (10,4%); statistical endurance of muscles of the abdominal press (69,8%) and back (72,4%); speed of visual information processing (42,4 %); concentration and stability of attention (30,4%), distribution and switching attention (27,6%); mobility of nerve processions (9,3%); operational and arbitrary memory (14,9% and 85,8%).